METHODS FOR VALUING A COMPANY IN THE SYSTEM OF VALUE-BASED MANAGEMENT (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. The study of methods for valuing business within the framework of value-based management (VBM) is of significant importance in modern business and finance. As companies strive to enhance their value through more effective management approaches, VBM has gained prominence. One critical component of this system is the accurate valuation of the business, which provides a basis for strategic decision-making and performance measurement. The article addresses the gaps in understanding and application of these methods in the context of the Ukrainian market, where specific challenges arise due to differences in legal frameworks, market conditions, and valuation practices.The Purpose of the Article. This article comprehensively reviews the current methods for valuing businesses within the value-based management system, with a particular focus on their applicability and limitations in the Ukrainian context. This involves evaluating both international best practices and the specifics of the national legislation and market environment that shape business valuation practices.Methods. The research employs a systematic approach to assess the key valuation methods used in value-based management. These include economic value added (EVA), and market value added (MVA), among others. The study uses both qualitative and quantitative methods, combining theoretical analysis with empirical insights drawn from current practices in Ukraine. The analysis also reviews the existing legal framework concerning business valuation, highlighting potential challenges and discrepancies in the current implementation.Results. The study identifies several critical aspects of business valuation within the VBM framework, particularly focusing on the need for a more harmonized approach between international practices and local regulations. It was found that while the primary methods of business valuation are widely recognized, their practical implementation in Ukraine faces challenges due to gaps in legal provisions and a lack of standardization in valuation practices. Moreover, the research highlights the necessity for businesses to adjust their valuation approaches to better align with international standards.Conclusions. The findings indicate that there is a significant need for further development of business valuation methods tailored to the Ukrainian market. The article concludes with recommendations for policymakers and practitioners to enhance the integration of international valuation methodologies within the Ukrainian regulatory and economic environment. This includes revising current legislation to ensure a more consistent application of valuation standards, as well as educating stakeholders on the practical application of these methods.
Keywords: business valuation, value-based management, economic value added, market value added, Ukraine, financial management, valuation methods.